Postinoculation Protozoan Establishment and Association Patterns of Methanogenic Archaea in the Ovine Rumen - Ohene-Adjei, Samuel (American Society for Microbiology, 2007)
Association patterns between archaea and rumen protozoa were evaluated by analyzing archaeal 16S rRNA gene clone libraries from ovine rumen inoculated with different protozoa. Five protozoan inoculation treatments, fauna free (negative control), holotrich and cellulolytic protozoa, Isotricha and Dasytricha spp., Entodinium spp., and total fauna (type A) were tested. We used denaturing gradient gel electrophoresis, quantitative PCR, and phylogenetic analysis to evaluate the impact of the protozoan inoculants on the respective archaeal communities. Protozoan 18S ribosomal DNA clone libraries were also evaluated to monitor the protozoal population that was established by the inoculation. Phylogenetic analysis suggested that archaeal clones associated with the fauna-free, the Entodinium, and the type A inoculations clustered primarily with uncultured phylotypes. Polyplastron multivesiculatum was the predominant protozoan strain established by the holotrich and cellulolytic protozoan treatment, and this resulted predominantly in archaeal clones affiliated with uncultured and cultured methanogenic phylotypes (Methanosphaera stadtmanae, Methanobrevibacter ruminantium, and Methanobacterium bryantii). Furthermore, the Isotricha and Dasytricha inoculation treatment resulted primarily in archaeal clones affiliated with Methanobrevibacter smithii. This report provides the first assessment of the influence of protozoa on archaea within the rumen microbial community and provides evidence to suggest that different archaeal phylotypes associate with specific groups of protozoa. The observed patterns may be linked to the evolution of commensal and symbiotic relationships between archaea and protozoa in the ovine rumen environment. This report further underscores the prevalence and potential importance of a rather large group of uncultivated archaea in the ovine rumen, probably unrelated to known methanogens and undocumented in the bovine rumen.